Infrared Spectrophotometry in Studies on Herbal Drug Triphala Churna - Anagha S. Bahulikar, Mrs.; R.V. Kashalkar, Mrs.; Pundlik, M.D. (Asian Journal of Chemistry, 2010)
Infrared spectrophotometry is a useful analytical technique for the identification of drugs and is recommended as one of the parameters for testing in various pharmacopoeias. At present the Ayurvedic Pharmacopoeia is not referring to sophisticated instrumental analytical techniques for the purpose of characterization and identification of Ayurvedic formulations. The present work demonstrates the utility of the IR spectrophotometry in the identification and characterization of Triphala. based on typical characteristic IR frequencies for identifying the herbal drug.